Smart Classroom Environment using IoT in advanced and lebanese French university Education - et. al., Nikita Sukare, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
When teachers go to the classroom, all the materials needed to conduct the lesson are taken with a piece of chalk, pen, pencil and notebooks, the notes are wasted without any modern technology and it is very difficult for a large number of students in the class to have too much contact. On average, we spend about 1,200 hours on Iraqi Kurdistan Airbnb students, with the help of interactive whiteboards, projectors, and writing boards, so that students can easily manage a lot of exercises that are easy to understand, with easy-to-understand tutorials, photos, and videos. Let's do it. These technologies will help teachers in the most effective manner to solve the most challenging solve the doubts not waste time. Then, these methods will help the teachers to change the classroom approach and make the students easily understand the lessons